Respuesta :
The x-intercept the value of x when y=0, i.e.
y=x^2+6x-17=0
The expression does not have rational factors, so we will resort to the quadratic equation to solve for x.
A=1
B=+6
C=-17
x=(-B +/- sqrt(B^2-4AC) ) / (2A)
=(-6 +/- sqrt(36+68) )/ (2)
=-3 +/- sqrt(26)
or
x=-3+sqrt(26) or -3-sqrt(26) [intercepts of x]
The y-intercept of the equation is solving for y after setting x to zero.
i.e.
y=x^2+6x-17 when x=0
I'll leave this last task for you so as not to bore you!
y=x^2+6x-17=0
The expression does not have rational factors, so we will resort to the quadratic equation to solve for x.
A=1
B=+6
C=-17
x=(-B +/- sqrt(B^2-4AC) ) / (2A)
=(-6 +/- sqrt(36+68) )/ (2)
=-3 +/- sqrt(26)
or
x=-3+sqrt(26) or -3-sqrt(26) [intercepts of x]
The y-intercept of the equation is solving for y after setting x to zero.
i.e.
y=x^2+6x-17 when x=0
I'll leave this last task for you so as not to bore you!
Answer:
-8.09 2.09 -17
Step-by-step explanation:
Those are the three blanks